Analisis Penguatan Profil Pembelajaran Pancasila Dimensi Gotong Royong Pada Kurikulum Merdeka Kelas V SDN 1 Pagerageung - Sihabul Milah, Milki; Sutisna, Atang; Nurfirdaus, Nunu (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2025)
This research aims to determine the results of the Strengthening Analysis of the Pancasila Dimension Learning Profile Mutual Cooperation in the Independent Curriculum for Class V SDN 1 Pagerageung. The research design uses qualitative research with an explanatory case study type of research. The research subjects consisted of teachers, school principals, and 10 students. Data collection techniques use interviews and questionnaires. The data analysis technique goes through the stages of data reduction, data presentation, and drawing conclusions. The results of the research show that strengthening the Pancasila learning profile of the integrated mutual cooperation dimension in the Merdeka Curriculum in Class V of SDN 1 Pagerageung has been carried out well. This can be seen from the efforts made by teachers and school principals in supporting these activities. Teachers in their strengthening efforts use references from various references or sources. The school principal with his policy provides facilities and infrastructure that can support improving the quality of learning. Students' understanding of the value of mutual cooperation applied through Pancasila learning in Class V of SDN 1 Pagerageung is on average good.